Iowa CBC reporting form, DeSoto National Wildlife Refuge, January 4, 1986 - Drews, K. L.et al (1986)
Checklist dated January 4, 1986 compiled by Karen Drews. A list of birds sighted by Drews and twenty-six others at the DeSoto National Wildlife Refuge. A total of 57 species and 32,955 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed